2013
DOI: 10.1007/s11102-013-0529-6
|View full text |Cite
|
Sign up to set email alerts
|

Adult mortality or morbidity is not increased in childhood-onset growth hormone deficient patients who received pediatric GH treatment: an analysis of the Hypopituitary Control and Complications Study (HypoCCS)

Abstract: BackgroundThe French Safety and Appropriateness of Growth Hormone treatments in Europe (SAGhE) cohort has raised concern of increased mortality risk during follow-up into adulthood in certain patients who had received growth hormone (GH) treatment during childhood. The Hypopituitary Control and Complications Study monitored mortality and morbidity of adult GH-deficient patients including those with childhood-onset GH deficiency (COGHD) who received GH treatment as children.PurposeEvaluate risk of mortality, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 20 publications
(36 reference statements)
3
30
0
1
Order By: Relevance
“…These findings suggest that GH treatment in children is not associated with cardiovascular changes measurable with cIMT. Our observation is in line with reports that adult mortality and morbidity is not higher in childhood-onset GH-deficient patients who received pediatric GH treatment [33,34] . Our study demonstrated a relationship between changes in cIMT, IGF-1, and IGFBP-3 in univariate analyses.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that GH treatment in children is not associated with cardiovascular changes measurable with cIMT. Our observation is in line with reports that adult mortality and morbidity is not higher in childhood-onset GH-deficient patients who received pediatric GH treatment [33,34] . Our study demonstrated a relationship between changes in cIMT, IGF-1, and IGFBP-3 in univariate analyses.…”
Section: Discussionsupporting
confidence: 93%
“…The relative risk of subsequent neoplasm, however, in the GH-treated CCSS subjects was initially estimated at 3.21 (95% CI: 1.88-5.46) [47], but was lowered to 2.15 (95% CI: 1.3-3.5) with a longer follow-up period [48]. Similar results have also been observed in several GH post-marketing studies [14,15,49]. In the GeNeSIS and HypoCCS post-marketing studies [50], overall 5-year cumulative incidence of subsequent neoplasms in GH-treated pediatric cancer survivors was estimated to be 6.2%, which was similar to the earlier CCSS findings [47,48].…”
Section: Acromegalysupporting
confidence: 79%
“…Conversely, the SAGhE data from Sweden, Belgium and the Netherlands did not demonstrate any evidence of changes in death rates from cancer [12]. More recent pharmaco-surveillance studies from the Pfizer International Metabolic Database (KIMS) [13] and Hypopituitary Control and Complications Study (HypoCCS) [14,15] cohorts have provided further reassurance concerning the risk of cancer occurrence in GH-deficient adults treated with GH replacement therapy. Thus, the safety of long-term GH therapy in association with cancer risk based on current published evidence remains inconclusive.…”
mentioning
confidence: 99%
“…A later publication by Poidvin et al (13) documented an increased risk of stroke, particularly hemorrhagic stroke, among patients diagnosed with GHD, ISS, or born SGA and treated with GH during childhood, compared with two populationbased registries (standardized incidence ratio from 3.5 to 7.0). By contrast, other reports have not documented any significant impact of GH treatment during childhood (14,15,16). No deaths from cancer or cerebrovascular causes were reported among the 2543 patients in the SAGhE study results from Belgium, the Netherlands, and Sweden (14).…”
Section: Introductionmentioning
confidence: 77%
“…No deaths from cancer or cerebrovascular causes were reported among the 2543 patients in the SAGhE study results from Belgium, the Netherlands, and Sweden (14). Furthermore, no increased risk of mortality or incidence of cancer, stroke, or myocardial infarction in adult GHD patients who had previously received GH therapy during childhood was reported in 1204 patients enrolled in Hypopituitary Control and Complications Study (HypoCCS) (15), and data from a cohort of 494 patients from a Danish population-based registry study with childhood-onset GHD did not reveal a relationship between childhood GH therapy and death due to cerebrovascular events (16). Thus, the long-term safety of GH therapy during childhood remains inconclusive and deserves further investigation (17,18,19,20).…”
Section: Introductionmentioning
confidence: 99%